2022
DOI: 10.3390/jmse10030442
|View full text |Cite
|
Sign up to set email alerts
|

Feedback between Basin Morphology and Sediment Transport at Tidal Inlets: Implications for Channel Shoaling

Abstract: Increasing societal pressures (e.g., population growth and urbanization) are driving land use change practices in coastal areas that could potentially alter the hydrodynamics and sediment transport patterns near coastal inlets in ways that might exacerbate existing shoaling conditions. To investigate the potential impact of coastal development, a numerical model is used to predict the long-term evolution of an idealized lagoonal-type barrier island inlet under five different morphological conditions that trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This asymmetry in tidal currents influences the sediment budget through an asymmetry of fluctuating tidal current speed and rest flow duration [23]. These modifications can alter flow pathways and control the trend of geomorphic evolution, to a certain extent [24]. Previous studies have demonstrated that when a tidal gate is built at the mouth of an estuarine tributary, the downstream sediment deposition mainly depends on the position of the trunk channel.…”
Section: Introductionmentioning
confidence: 99%
“…This asymmetry in tidal currents influences the sediment budget through an asymmetry of fluctuating tidal current speed and rest flow duration [23]. These modifications can alter flow pathways and control the trend of geomorphic evolution, to a certain extent [24]. Previous studies have demonstrated that when a tidal gate is built at the mouth of an estuarine tributary, the downstream sediment deposition mainly depends on the position of the trunk channel.…”
Section: Introductionmentioning
confidence: 99%